Sunteți pe pagina 1din 23

Mechanics

Physics 151

Mechanics Physics 151 Lecture 23 Continuous Systems and Fields (Chapter 13)

Lecture 23

Continuous Systems and Fields (Chapter 13)

Where Are We Now?

Where Are We Now? We’ve finished all the essentials Final will cover Lectures 1 through 22

We’ve finished all the essentials

Final will cover Lectures 1 through 22

Last two lectures: Classical Field Theory

Start with wave equations, similar to Physics 15c Do it with Lagrangian, and maybe with Hamiltonian Go into relativistic field theory

Not enough time to discuss everything

Let’s see how much we can do And take it easy!

Longitudinal Mechanical Waves

Longitudinal Mechanical Waves An infinite elastic rod is vibrating longitudinally dx x Model this with a

An infinite elastic rod is vibrating longitudinally

dx

Waves An infinite elastic rod is vibrating longitudinally dx x Model this with a chain of

x

Model this with a chain of masses and springs Did this in 15c ∆x m
Model this with a chain of masses and springs
Did this in 15c
∆x
m
k
η
i

i-th mass’s position is η i relative to equilibrium

T =

i

2

1 mη
2

i

i

1 k η η
2

V =

(

i

+ 1

i

2 ) Let’s build the Lagrangian
2
)
Let’s build the
Lagrangian

Lagrangian

Lagrangian L = ∑ i ∑ = i 1 2 2 ⎡ −− mk ( η

L

=

i

=

i

1 2 2 ⎡ −− mk ( η ηη ) ⎤ ⎣ i ii +
1
2
2
⎡ −−
mk (
η
ηη
)
i
ii
+ 1
2
2
1
m
η
η
2
i
+ 1
i
η
−∆ kx
i
2
∆ x
⎝ ⎜
∆ x
⎟ ⎠
⎥ ⎦

x

Lagrangian is

Rearrange a little
Rearrange
a little

m/x is the linear density µ (mass/unit length) kx is the elastic modulus K (force/fractional elongation)

x is the elastic modulus K (force/fractional elongation) Think about Hooke’s law L L F =−∆

Think about Hooke’s law

L

L

F

=−∆ =−

k

L

K

It’s not Young’s modulus

How much the spring is stretched relative to its natural length
How much the spring is stretched
relative to its natural length

µ and K remain constant as we shrink x 0

Continuous Limit

Continuous Limit Now we have ⎡ 1 ⎛ η − η 2 ⎤ ⎞ 2 LKx

Now we have

⎡ 1 ⎛ η − η 2 ⎤ ⎞ 2 LKx = ∑ i +
1
η
η
2 ⎤
2
LKx
=
i
+ 1
i
2
i
µη
i
⎝ ⎜
∆ x
⎟ ⎠
⎥ ⎦
Re-label η i with the equilibrium position x η→η x ( ) i 2 1
Re-label η i with the equilibrium position x
η→η x
(
)
i
2
1
η
(
xx +∆ ) −
η
() ⎞
x
2
L
=−
µη
(
xK
)
∆ x
2
⎜ ⎝
x
⎟ ⎠
i
⎦ ⎥
2
1
η
d
∆→ 0
x
2
Shrink!
⎯⎯⎯→
µη
− K
dx
2
⎜ ⎝
dx
⎟ ⎠
⎦ ⎥
Lagrangian per unit length

Lagrangian Density

Lagrangian Density We can write the Lagrangian as 2 2 1 ⎡ ⎛⎞ d η ⎤

We can write the Lagrangian as

2 2 1 ⎡ ⎛⎞ d η ⎤ ⎛⎞ d η L = ∫ ⎢
2
2
1
⎛⎞
d
η
⎛⎞
d
η
L =
µ
−≡
K
dx
∫ L
dx
2
⎝⎠ ⎜⎟ dt
⎝⎠ ⎜⎟ dx
⎦ ⎥

L is the Lagrangian density in 1-dimension

We may generally extend this to 3-dimensions

L =

∫∫∫ L

dxdydz

where

L =

1

⎛⎞

d

η

2

Y

d

η

2

ρ

⎝⎠ ⎜⎟ dt

⎛⎞

⎝⎠ ⎜⎟ dx

2

⎥ ⎦

ρ is the volume density µ/A (A is the rod’s cross section) Y is Young’s modulus K/A

Lagrange’s Equations

Lagrange’s Equations First, start from Do the usual ⎡ 1 ⎛ η − η 2 ⎤

First, start from

Do the usual

⎡ 1 ⎛ η − η 2 ⎤ ⎞ 2 LKx = ∑ µη i
1
η
η
2 ⎤
2
LKx
=
µη
i
+ 1
i
i
2
⎝ ⎜
∆ x
⎠ ⎟
i
⎣ ⎢
⎦ ⎥

Lagrange’s equations

 

L

=

K

η

i

+

1

η

i

⎞⎛ K

+

−⎤

1

ηη

ii

∆= 0

dL ⎛ ∂ ⎞ ⎜

dt

η

i

 

η

i

µη

∆∆ x ⎝ ⎜ x

 

⎟⎜

⎠⎝

∆∆

x

x

⎟⎥ ⎠⎦

x

Shrink µη − ∆x
Shrink
µη
∆x

K

d 2

η

dx

2

= 0

v =

K

µ

That’s wave equation with velocity

We want to get this from the continuous Lagrangian

Lagrange’s Equations

for each i
for each i
Lagrange’s Equations for each i     ∂ Ld ∂ η i − dt ⎛∂ L
   

Ld

η

i

dt

⎛∂ L ⎞ ⎜

η

i

=

0

Ld

 

=

0

 
 

 

()

η x

 

dt

⎛ ∂ L

()

η x

 

In the discrete case, we had

η i became η(x) Simple analogy gives

But this doesn’t work

We must go back to Hamilton’s Principle

2

1

2

∫∫ L

1

 

dxdt = 0

δδI = Ldt = δ

Hamilton’s Principle

Hamilton’s Principle   L = 1 ⎡ ⎢ ⎛⎞ d η 2 − K ⎛⎞ d
 

L

=

1

⎛⎞

d

η

2

K

⎛⎞

d

η

2

 

2

µ

⎝⎠ ⎜⎟ dt

⎜⎟

⎝⎠ dx

⎥ ⎦

(

L=Lη ,

d

η

dx

,

d

η

dt

x t

,,

)

 

Our Lagrangian density is

Let’s get general L may depend on

We need the “path” of η and its variation

η(xt, ;αη) = (xt, ;0) +αζ (xt, )

η ( xt , ; αη ) = ( xt , ;0) + αζ ( xt
η ( xt , ; αη ) = ( xt , ;0) + αζ ( xt

Will make α 0

Nominal path

Variation

Set variation to zero at the boundaries

ζζζζ(,xt ) ====(,xt ) (x ,)t (x ,)t 0

1

21

2

(, xt ) ==== (, xt ) ( x ,) t ( x ,) t 0
Final
Final
) ==== (, xt ) ( x ,) t ( x ,) t 0 1 21
) ==== (, xt ) ( x ,) t ( x ,) t 0 1 21
Initial
Initial
Edges
Edges

OK, let’s work…

Don’t really matter for the infinite rod
Don’t really
matter for the
infinite rod

Hamilton’s Principle

Hamilton’s Principle dI d x 2 2 ( d η d η = ∫∫ t L
dI d x 2 2 ( d η d η = ∫∫ t L η
dI
d
x
2
2
(
d
η
d
η
=
∫∫ t
L
η
,
,
,,
x t
)
dxdt
dx
dt
d
α
d
α
t
x
1
1
d
η
d
η
⎧∂∂
η
x
LL
d
d
∂ L
d
2
2
dx
dt
=
∫∫ t
++
dxdt
d
η
d
η
t
x
∂∂
ηα
dd
α
d
α
1
1
dx
dt
LL
d
⎛⎞
x
⎪∂∂
dd
⎛⎞⎫
∂ L ⎪
η
2
2
=
∫∫ t
−−
dxdt
⎜⎟
⎜⎟⎬
d
η
d
η
t
x
∂∂
η
dx
dt
d
α
1
1
⎝⎠
⎝⎠⎪
dx
dt

Hamilton’s Principle gives

dI

=

t

∫∫

2

x

2

⎪∂∂

⎛⎞

LL

d

−−

d

⎛⎞⎫

⎜⎟⎬

⎝⎠⎪

L

d

η

dt

ζ

(,) x t

dxdt =

0

d

α

⎠ ⎟

α

= 0

t

1

x

1

⎜⎟

⎝⎠

∂∂

η

dx

d

η

dx

dt

 

= 0!

Lagrange’s Equation

Lagrange’s Equation Lagrange’s equation for the 1-dim problem is ⎛⎞∂ L ⎛⎞∂∂ LL ⎜⎟ ⎝⎠ d

Lagrange’s equation for the 1-dim problem is

⎛⎞∂ L

⎛⎞∂∂ LL ⎜⎟

⎝⎠

d

+

d

dt

⎜⎟

d

η

dx

d

η

∂∂

⎝⎠

dt

dx

η

= 0

dx d η ∂∂ ⎝⎠ dt dx η = 0 Let’s try it with 2 2

Let’s try it with

2 2 1 ⎡ ⎛⎞ d η ⎛⎞ d η ⎤ L = 2 ⎣
2
2
1 ⎡
⎛⎞
d
η
⎛⎞
d
η
L =
2 ⎣
µ
− K
⎝⎠ ⎜⎟ dt
⎝⎠ ⎜⎟ dx
⎥ ⎦

dd

η

⎞⎛ d

K

d

η

d

2

d

2

ηη

K

=−

dt

⎜ ⎝

µ

dt

⎟⎜

⎠⎝ dx

 

dx

⎟ ⎠

µ

dt

2

 

dx

2

= 0

Yes, the right wave equation
Yes, the right
wave equation

3-D Version

3-D Version Easy to guess how it should look like in 3-dim. ( L = L

Easy to guess how it should look like in 3-dim.

(

L=Lη ,

dddd

ηηηη

dx

,

dy

,

dz

,

dt

xyzt

,,,,

)

I =

txyz

∫∫∫∫

22

22

txyz

11

11

y z t dxdydzdt

L (

η

,

dddd

ηηηη

dx

,

dy

,

dz

,

dt

x

,,,,

)

⎛⎞∂

L

⎛⎞∂

L

⎛⎞∂∂ LL

dddd

L

−= 0

∂∂

η

+ + ⎜⎟ ⎜⎟ ⎟+ ⎟ ⎜⎟ dddd ηηηη dt ∂ dx ∂ dy ∂
+
+
⎜⎟
⎜⎟
⎟+ ⎟
⎜⎟
dddd
ηηηη
dt
dx
dy
dz
⎝⎠
⎝⎠
⎝⎠
dt
dx
⎜ ⎜ ⎝
dy
dz

Symmetric between time and space Hope for relativistic formalism Will look into this in the next lecture

Multi-Component Field

Multi-Component Field I defined η as the displacement along x axis General 3-dim. vibration may be

I defined η as the displacement along x axis

General 3-dim. vibration may be in any direction

η
η

η=η η η

x

y

z

(,

,)

We are now dealing with 3 functions of space and time

L = L

dddd ηηηη ⎛ η ,,,,, xxxx x dx dy dz dt ⎜ ⎜ dddd ηηηη
dddd
ηηηη
η
,,,,,
xxxx
x
dx
dy
dz
dt
dddd
ηηηη
η
yyyy
,,,,,
y
dx
dy
dz
dt
dddd
ηηηη
η
,,,,,
zzzz
z
dx
dy
dz
dt
xyzt ,,,

⎞ ⎟ ⎟ ⎟ ⎟ ⎟ ⎟ ⎠

,,,,, zzzz z dx dy dz dt ⎜ ⎜ xyzt ,,, ⎝ ⎞ ⎟ ⎟ ⎟
This is getting really tedious
This is getting really tedious

Shorthand Notation

Shorthand Notation Let’s use indices (0,1,2,3) instead of t , x , y , z Similar

Let’s use indices (0,1,2,3) instead of t, x, y, z

Similar to what we did in relativity

We need quantities like

Let’s get lazy

η i
η
i

dx µ

d

η

i

d

η

ρ

η

,

ρµ

dx

µ

d

2 η

ρ

η

ρ µν

,

dx dx

µ

ν

and

d 2 η i dx dx µ ν
d
2 η
i
dx dx
µ
ν

η

,

µ

d

η

dx

µ

etc.

We can write, e.g.

(

L=Lη η

ρ

,

, x

ρµ µ

,

)

d

L

L

dx µ

η

ρµ

,

⎟− ⎟

η

ρ

= 0

Conservation Laws

Conservation Laws Let’s try what we did with the energy function Consider the total derivative of

Let’s try what we did with the energy function

Consider the total derivative of the Lagrangian density

(

Lηη

,

,

µ

, x

µ

)
)
∂ L ∂ L d LL =+ ∂ η η + , µ , µν
L
L
d LL =+ ∂
η
η
+
,
µ
,
µν
dx
η
η
∂ x
µ
, ν
µ

Using Lagrange’s equations:

d

L

L

dx µ

η

,

µ

⎠ ⎟

 

η

= 0

∂ η , µ ⎠ ⎟   ∂ η = 0 d L d ∂ L
d L d ∂ L = ⎛ ⎜ dx dx ∂ η µ νν ⎝
d
L
d
L
=
dx
dx
η
µ
νν
⎝ ⎜
,
⎠ ⎟ ⎟
η
++ ∂ LL ∂
η
,
µ
,
µν
η
∂ x
,
ν
µ
d
η
d
∂ L
L
,
µ
=
η
+
This is
,
µ
dx
η
∂ x
dx
ν
νν
,
⎠ ⎟
µ

Stress-Energy Tensor

Stress-Energy Tensor We got d ⎛ ⎜ ∂ L   − L δ ⎞ ⎟ =−

We got

d

L

 

L

δ

=−

L

dx

ν

η

,

ν

η

,

µ

µν

x

µ

≡ Stress-energy tensor T µν
Stress-energy tensor
T µν

NB: T µν is not a tensor in the relativistic sense

Suppose L does not depend explicitly on x µ

For µ = 1, 2, 3, that means no external force For µ = 0, that means no source/sink of energy

force For µ = 0 , that means no source/sink of energy dT µν dx ν

dT

µν

dx

ν

= 0

What does this “conservation” condition mean?

Free field
Free
field

Divergence of S-E Tensor

Divergence of S-E Tensor   dT µν = 0     dx ν   dT µν
 

dT

µν

= 0

 
 

dx

ν

 

dT

µν

=

dT

µ

0

+

dT

µ

i

=

dT

µ

0

+∇⋅ T = 0

dx

ν

dt

dx

i

dt

µ

The condition

has a form of divergence

Integrate over a fixed volume V and use Gauss’s Law

d ∫∫ T dV = − ∇⋅ T dV =− ∫ TS d ⋅ µ
d
∫∫
T
dV
= − ∇⋅
T
dV
=−
TS d
µ
0
µµ
What escapes
from the surface
dt
Total T µ0
in the volume
This vector represents
the “flow”

Now we need to know what T µ0 and T µ are

Energy Density

∂ L ≡ η − L δ T µν , µ µν ∂ η ∂
L
η
L
δ
T µν
,
µ
µν
η
L
,
ν
First consider
T
=
η
− L
00
η
Looks just like the energy function, doesn’t it?
Think about the 1-dim. elastic rod example
2
2
2
2
1
⎛⎞
d
η
⎛⎞
d
η
1
⎛⎞
d
η
⎛⎞
d
η
L
=
µ
K
T
=
µ
+
K
⎜⎟
⎜⎟
⎜⎟
⎜⎟
00
2
⎝⎠
dt
2
dx
⎝⎠
dx
dt
⎝⎠
⎝⎠
⎦ ⎥
⎥ ⎦

T 0 should be the energy flow

01

dx

L

d

η

T

=

K

η

=−

η

d

η

dx

is it?

Kinetic

energy

Potential energy
Potential
energy

Energy Current Density

Energy Current Density Consider a small piece dx It’s stretched by η +− η = d

Consider a small piece

dx

Energy Current Density Consider a small piece dx It’s stretched by η +− η = d

It’s stretched by

η +−η =

d

η

dx

(

x

dx

)

x

()

dx

η = d η dx ( x dx ) x () dx This gives the Hooke’s

This gives the Hooke’s law force

η(x) η(x + dx)

F

=−

K

d

η

dx

The work done by this piece to the next piece is

d

η

dx

F

η =−

K

η

equals to
equals to

d

η

T

01

 

K

=−

η

dx

Momentum Density

L

T µν

η

,

 

L

δ

µ

µν

η

, ν

  − L δ µ µν ∂ η , ν First consider T i 0 ∂

First consider

T i0

L d

η

=

η

dx

i

Again with the 1-dim. elastic rod example

L =

1

⎛⎞

d

η

2

K

d

η

2

µ

⎜⎟

⎝⎠ dt

⎛⎞

⎝⎠ ⎜⎟ dx

2

⎤ ⎥ ⎥ ⎦
⎥ ⎦

This isn’t so obvious…

d

d

η η

dt

dx

T

10

=µ

Momentum Density

T

d

d

η η

=µ 10 dt dx
10
dt
dx

How much mass is there between x and x + dx?

µdx to the zeroth order To the first order

µ

d

η

⎜ ⎝

1

dx

⎟ ⎠

dx

dx

d η ⎞ ⎜ ⎝ 1 − dx ⎟ ⎠ dx dx It’s velocity is η
d η ⎞ ⎜ ⎝ 1 − dx ⎟ ⎠ dx dx It’s velocity is η

It’s velocity is

η
η

,

so the momentum is

⎝ ⎜

dx

⎠ ⎟

dt

µ

1

d

d

η η

µ ⎛ 1 − d ⎞ d η η dx
µ ⎛ 1 − d ⎞ d η η dx

dx

η(x) η(x + dx)

Density of excess momentum is

µ

d

d

η η

dt

dx

=− T

10

T 10 may be considered as the momentum density

Stress-Energy Tensor

Stress-Energy Tensor We can interpret the stress-energy tensor T µ ν as T 0 0 =

We can interpret the stress-energy tensor T µν as

T 00 = energy density T 0i = energy current density T i0 = momentum density T ij = momentum current density

The divergence condition

dT

µν

dx

ν

= 0

represents

conservation of energy and momentum

Summary

Summary Built Lagrangian formalism for continuous system L = ∫∫∫ L dxdydz Lagrangian Lagrange’s equation

Built Lagrangian formalism for continuous system

L =

∫∫∫ L

dxdydz

Lagrangian

Lagrange’s equation Derived simple wave equation

d

L

L

dx

µ

η

,

µ

⎟ ⎟ ⎠

η

= 0

Energy and momentum conservation given by the

energy-stress tensor

Conservation laws

L

T µν

η

,

 

L

δ

µ

µν

η ,

ν

  − L δ µ µν ∂ η , ν dT µν dx ν = 0

dT

µν

dx

ν

= 0

take the form of (time derivative) = (flux into volume)